Bias Correction of Paleoclimatic Reconstructions: A New Look at 1, 200+ Years of Upper Colorado River Flow. Issue 1 (17th January 2020) - Robeson, Scott M.; Maxwell, Justin T.; Ficklin, Darren L.
Abstract: Bias correction, while widely used with climate‐model output, is not typically applied to paleoclimatic reconstructions. While many reconstruction models have low average error, they still may contain bias, especially in the tails of distributions. Bias correction, used cautiously, can be a valuable procedure that alters interpretations of past events. Analyzing the iconic tree‐ring reconstruction of Upper Colorado River flow, we find that its probability distribution is markedly different from that of observed flow. Using quantile mapping to bias correct the reconstruction, we analyze the full reconstructed record and two events in particular: the 1100s megadrought and the early 1600s pluvial. Overall, bias correction made the 1100s megadrought, the largest in the 1, 200+year record, even more extreme. After bias correction, the early 1600s pluvial marginally exceeds the early twentieth century pluvial in magnitude but not in duration. Overall, bias correction should be considered whenever paleoclimatic reconstructions are compared directly to observations. Plain Language Summary: To study past climates, scientists use indicators such as tree‐ring widths that are related to temperature, precipitation, or streamflow. While these indicators usually are very reliable, they sometimes do not perform as well with extreme events such as intense droughts and wet periods. Here, we adopt a method that can correct for these limitations and apply it to a 1, 200+year record of streamflow for the Upper Colorado River, a critical source of water for much of the southwestern United States. After using our method, we find that several extreme events from the tree‐ring record of streamflow were even more intense than formerly thought. In particular, the largest drought in the record that occurred during the 1100s was drier and longer lasting after our correction. During the 56‐year duration of the 1100s drought, our correction makes the flow in the river lower by nearly 52 × 10 9 m 3 of water, which is the equivalent of 1.45 times the capacity of Lake Mead (the largest reservoir in the United States). And, while it was known that the early 1900s was among the wettest periods in the last 1, 200+ years, we identify a period in the early 1600s that matches it. Key Points: Bias correction makes paleoclimatic models more comparable to observations After bias correction, the 1100s Colorado River megadrought became more extreme The early 1600s Colorado River pluvial rivals that of the early twentieth century after bias correction